Embedded fluid transfer membrane, preparation method and application

By filling metal paste on the side of the metal sintered felt to form an embedded fluid transport film, the problem of insufficient contact area between the fluid transport film and the catalyst in the prior art is solved, the electrolytic efficiency is improved and the catalyst usage is reduced.

CN119194508APending Publication Date: 2024-12-27GUANGDONG XINLI NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310725820.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Due to the rough surface of the porous titanium transport membrane in the existing proton exchange membrane electrolytic cells, the porous titanium transport membrane reduces the effective contact area between the fluid transport membrane and the catalyst, resulting in low electrolytic efficiency and high catalyst usage.

Method used

By filling the pores on the side of the metal sintered felt, drying, degreasing and sintering, an embedded fluid transport film is formed, increasing the effective contact area between the fluid transport film and the catalyst, while maintaining high porosity to ensure breathability.

Benefits of technology

The electrolytic efficiency is improved, the amount of expensive catalyst is reduced, and strength and toughness are enhanced through the composite structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194508A_ABST
    Figure CN119194508A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an embedded fluid transfer membrane, which comprises the following steps: step 1, metal slurry is infiltrated from the surface of a metal sintered felt, and the infiltration depth is smaller than the thickness of the metal sintered felt; 2, after permeation is finished, the metal slurry remaining on the surface of the metal sintered felt is removed, and a blank film is obtained; and step 3, drying, degreasing and sintering the blank film to obtain the embedded fluid transmission film. The invention further provides an embedded fluid transfer membrane which comprises a composite fiber layer and an embedded layer, the fiber layer comprises a first metal sintered felt, the embedded layer comprises a second metal sintered felt and a metal powder sintered body embedded in pores in the side, away from the first metal sintered felt, of the second metal sintered felt, and the surface roughness Ra of the side is smaller than or equal to 7 micrometers. The invention also relates to an application in an ion exchange membrane electrolytic tank. The air permeability is guaranteed, meanwhile, the surface roughness is reduced, the effective contact area of the fluid transfer membrane and the catalyst is increased, the electrolytic efficiency is finally improved, and the consumption of the expensive catalyst is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane materials, and in particular relates to an embedded fluid transmission membrane, a preparation method and an application thereof. Background Art

[0002] The proton exchange membrane electrolyzer (PEMWE) is mainly composed of a membrane electrode composed of a proton exchange membrane, a catalyst and a gas diffusion layer, a bipolar plate and a sealing ring, a protective sheet, an end plate, etc. The PEM electrolyzer requires an external DC power supply when working. The anode represents the positive electrode of the electrolyzer, where an oxidation reaction (oxygen evolution) occurs, and the cathode represents the negative electrode of the electrolyzer, where a reduction reaction (hydrogen evolution) occurs. In the electrolyzer for proton exchange membrane water electrolysis, the gas diffusion layer (i.e., porous transport membrane, fluid transport membrane) usually uses a thin sheet of porous titanium material to achieve conductivity while ensuring water and gas transmission. The porous titanium transport membrane is currently made by randomly laying titanium fibers into felt and then sintering them, and the surface of one side of the titanium felt is fitted and contacted with the catalyst. Metal felts such as titanium felt have excellent porosity and air permeability, but the surface is relatively rough, which reduces the effective contact area between the fluid transport membrane and the catalyst. Summary of the invention

[0003] In view of all or part of the deficiencies of the prior art described above, the object of the present invention is to provide an embedded fluid transport membrane, a preparation method and an application, which can reduce the surface roughness while ensuring air permeability, thereby increasing the effective contact area between the fluid transport membrane and the catalyst, and ultimately improving the electrolysis efficiency and reducing the amount of expensive catalyst used.

[0004] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing an embedded fluid transport membrane, comprising the following steps:

[0006] Step 1: infiltrating the metal slurry from the surface of the metal sintered felt, with the infiltration depth being less than the thickness of the metal sintered felt;

[0007] Step 2: After the infiltration is completed, the metal slurry remaining on the surface of the metal sintered felt is removed to obtain a green film;

[0008] Step three: drying, degreasing and sintering the green film to obtain an embedded fluid transport membrane.

[0009] The present invention fills the pores on one side of the metal sintered felt with metal slurry, dries to remove the solvent, degreases to remove the binder in the metal slurry, and sinters the metal particles in the metal slurry and the metal sintered felt into one body. There are two different porosities in the metal sintered felt. The infiltration surface of the metal slurry contacts the catalyst, and the metal particles are embedded (filled in the pores) on the surface of one side of the metal sintered felt, which reduces the surface roughness of the infiltration surface, increases the effective contact area between the fluid transport membrane and the catalyst, and reduces the amount of expensive catalyst. The metal particles and the metal sintered felt form a composite material structure, and the porosity of the composite material, i.e., the embedded side, is kept above 45%, but the strength and toughness are much higher than pure powder products with the same porosity, because the slender fibers act as reinforcing ribs. The high porosity can retain good air permeability and improve the electrolysis efficiency.

[0010] Compared with using a layer of metal sintered felt or a composite of multiple layers of metal sintered felt with different porosities / pore sizes / fiber diameters as a fluid transport membrane, the present invention can improve the catalytic efficiency by increasing the effective contact area with the catalyst; compared with using a layer of metal powder sintered layer or a composite of multiple layers of metal powder sintered layers with different porosities as a fluid transport membrane, the present invention increases the effective surface in contact with the catalyst by embedding metal powder on one side of the metal sintered felt surface, while ensuring the effective contact area and retaining good air permeability, and can also use the metal sintered felt to guide water and gas. Moreover, the preparation method of composite multiple layers of metal sintered felt / metal powder sintered layers with different porosities is relatively complicated; in order to maintain the smaller thickness of the fluid transport membrane, multiple layers of thinner metal sintered felt / metal powder sintered layers are composited, and its structural stability is affected.

[0011] Compared with using a metal powder sintered layer superimposed on a metal sintered felt as a composite layer, on the one hand, if the superimposed metal powder sintered layer is thicker, the total thickness of the fluid transfer membrane will increase, affecting the air permeability, and the structural strength will be affected. On the other hand, if the superimposed metal powder sintered layer is thinner in order to maintain a smaller thickness of the fluid transfer membrane, part of the metal powder sintered layer will fall into the pores of the metal sintered felt during the sintering process, resulting in many bumpy holes or holes on the contact surface with the catalyst, and the effective contact area is greatly reduced. If the penetration depth of the metal slurry is too deep and even reaches the other side surface of the metal sintered felt, that is, the entire metal sintered felt is filled with metal powder, the air permeability will be affected, and because there is no sintered felt mesh structure, it is not conducive to its water diversion effect. If the metal slurry is only cured without degreasing and sintering, its permeability cannot meet the requirements.

[0012] In step three, drying is performed in air or protective atmosphere, the drying temperature is from room temperature to 140 degrees, and the drying time is 2-12 hours; degreasing is performed under an inert gas or hydrogen as a protective atmosphere and a pressure of 0.5-10mbar, the degreasing temperature is 300-700 degrees, and the degreasing time is 2-24 hours; under a vacuum degree of 0.001Pa-1000Pa, the sintering temperature is 900-1200 degrees, and the sintering time is 2-12 hours. The degreasing temperature is selected according to the material of the binder, i.e., the glue, but generally speaking, the degreasing temperature should not be too high to avoid metal oxidation. By setting the sintering temperature and sintering time, the porosity can be determined in an appropriate range.

[0013] Furthermore, in step three, the drying condition is air drying at room temperature for 8-12 hours; in the degreasing condition, the inert gas is helium, argon or nitrogen, and the pressure is 1-5 mbar; and the sintering temperature is 980-1120 degrees.

[0014] In step 3, the green film is rolled after the sintering is completed. The thickness of the rolled felt body is 0.2-0.6 mm. Rolling can reduce the thickness deviation of the embedded fluid transport membrane.

[0015] In step 1, the preparation of the metal sintered felt is as follows: the metal fibers are laid into felt, and the first sintering and the first rolling are performed; under a vacuum degree of 0.001Pa-1000Pa, the first sintering temperature is 900-1200 degrees, and the first sintering time is 2-12 hours; the thickness of the felt body after the first rolling is less than or equal to 0.8mm. The first rolling can reduce the thickness deviation of the metal sintered felt, reduce its surface roughness and reduce the pore size, and can prevent the subsequent metal slurry from infiltrating too quickly and causing uneven distribution of metal powder.

[0016] The metal fiber includes the following metal fibers: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel; the diameter of the metal fiber is less than or equal to 30 μm; the thickness of the metal sintered felt is less than or equal to 0.6 mm, and the porosity is greater than or equal to 60%. If the porosity of the metal sintered felt is too small, it will affect the penetration of the metal slurry. The fiber diameter affects the pore size and roughness. Under the premise that the weight of the fiber per unit area has been determined and evenly distributed, the area weight determines the input material cost, and the thickness determines the porosity. The length of the metal fiber is preferably 5-30 mm.

[0017] In step one, the metal slurry is prepared by mixing 100 parts by weight of a solvent and 10-30 parts by weight of a binder (in a preferred embodiment, 1-10 parts by weight of an anti-settling agent may also be added), adding metal powder, and stirring evenly to obtain a slurry; the volume ratio of the metal powder to the slurry is 5%-35%. If the volume ratio of the metal powder in the slurry is too large, that is, the concentration of the metal particles is too high, it will make it difficult for the metal slurry to penetrate into the metal sintered felt, and the surface metal slurry cannot be scraped and removed; if the concentration of the metal particles is too low, the penetration efficiency is too low, and the penetration uniformity cannot be guaranteed. The weight ratio of the solvent, the binder and the anti-settling agent is 100:(10-30):(1-10), and more preferably 100:20:5.

[0018] The metal powder includes powders of the following metals: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel; the particle size of the metal powder is less than or equal to 55 μm. The solvent is alcohol, acetone or water, wherein the alcohol is preferably ethanol, ethylene glycol, etc. The binder is polyvinyl alcohol, polyethylene glycol or vinyl acetate. The anti-settling agent is, for example, the anti-settling agent product series of Deurheo and Arkema. If the particle size of the metal powder is too large, it will affect the penetration of the metal slurry, making it difficult for the metal powder to enter the internal pores of the metal sintered felt; therefore, in order to achieve embedding, most of the particles cannot be larger than the depression on the felt surface. Particles with too small a particle size are expensive, and strong activity can use a lower sintering temperature, but are easily contaminated by oxygen and carbon.

[0019] In step 1, the metal slurry is infiltrated into the metal sintered felt by spraying; the penetration depth of the metal slurry is less than or equal to 85% of the thickness of the metal sintered felt. Furthermore, the penetration depth of the metal slurry is 15%-50% of the thickness of the metal sintered felt. If the penetration depth is too deep, it will affect the air permeability / flowability and the guiding effect of the unfilled part on water and gas. If the penetration depth is too shallow, defects such as cracks may appear on the penetration surface of the metal sintered felt, and it is difficult to ensure the surface roughness of the penetration surface.

[0020] The present invention also provides an embedded fluid transport membrane, comprising a composite fiber layer and an embedding layer, wherein the fiber layer comprises a first metal sintered felt, and the embedding layer comprises a second metal sintered felt, and a metal powder sintered body embedded in the pores of the second metal sintered felt away from the first metal sintered felt. The metal powder sintered body is embedded on the surface of one side of the second metal sintered felt or in its interior, and there is no other material layer on the surface of the one side, so the second metal sintered felt and the metal powder sintered body are in direct contact with the catalyst. The filling of metal particles increases the effective contact area between the fluid transport membrane and the catalyst, thereby improving the catalytic efficiency. The pores between the metal particles and the metal sintered felt can also retain good air permeability, thereby improving the electrolysis efficiency.

[0021] The first metal sintered felt and the second metal sintered felt are integrated as a continuous complete felt body, that is, the first metal sintered felt and the second metal sintered felt are the same piece of metal sintered felt, and are only named to identify the embedded and non-embedded parts.

[0022] The metal powder includes powders of the following metals: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel; the first metal sintered felt and the second metal sintered felt are made of metal fibers laid into felts, and are made through first sintering and first rolling; the metal fibers include fibers of the following metals: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel. The first sintering and first rolling here are different from the above sintering and rolling for distinction.

[0023] The diameter of the metal fiber is less than or equal to 30 μm; the total thickness of the first metal sintered felt and the second metal sintered felt is 0.2-0.6 mm.

[0024] The second metal sintered felt is embedded with metal powder sintered bodies throughout. The thickness of the second metal sintered felt is 15-55% of the thickness of the first metal sintered felt. If the second metal sintered felt is too thick and has metal powder sintered bodies embedded inside, while the thickness of the first metal sintered felt is too small, the air permeability / flowability and the water diversion and transmission function will be affected. The thickness of the second metal sintered felt is further preferably 0.05-0.16 mm.

[0025] The surface roughness Ra of the second metal sintered felt away from the first metal sintered felt is less than or equal to 7 microns, and the surface in contact with the catalyst is relatively smooth. Its surface roughness is less than that of a simple metal sintered felt, but close to that of a simple powder sintered layer.

[0026] The present invention also provides the use of any embedded fluid transport membrane in the above technical solutions in an ion exchange membrane electrolyzer. Further, the ion exchange membrane electrolyzer can be selected as a proton exchange membrane electrolyzer.

[0027] Compared with the prior art, the present invention has at least the following beneficial effects: the present invention fills the pores on one side of the metal sintered felt with metal slurry, dries to remove the solvent, degreases to remove the binder in the metal slurry, and then sinters the metal particles in the metal slurry and the metal sintered felt into one. The infiltration surface of the metal slurry contacts the catalyst, and the filling of the metal particles increases the effective contact area between the fluid transport membrane and the catalyst, thereby reducing the amount of expensive catalyst. The metal particles and the metal sintered felt form a composite material structure, which keeps the porosity of the composite material, i.e., the embedded side, above 45%, but the strength and toughness are much higher than those of pure powder products with the same porosity, because the slender fibers act as reinforcing ribs. The high porosity can retain good air permeability and improve the electrolysis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the specific embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 It is a schematic flow diagram of a method for preparing an embedded fluid transport membrane of the present invention;

[0030] Figure 2 It is a schematic structural diagram of an embedded fluid transport membrane of the present invention;

[0031] Figure 3 It is a voltage-current density test diagram of the fluid transport membrane of Example 3 of the present invention and Comparative Example 1.

[0032] Reference numerals: 1 - fiber layer; 2 - embedding layer. DETAILED DESCRIPTION

[0033] The technical solutions in the specific embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] like Figure 1 As shown, the present invention provides a method for preparing an embedded fluid transfer membrane, comprising the following steps: step one, infiltrating metal slurry from the surface of metal sintered felt, wherein the infiltration depth is less than the thickness of the metal sintered felt; step two, after the infiltration is completed, removing the metal slurry remaining on the surface of the metal sintered felt to obtain a green membrane; step three, drying, degreasing and sintering the green membrane to obtain an embedded fluid transfer membrane.

[0035] and an embedded fluid transport membrane, e.g. Figure 2 As shown, it includes a composite fiber layer 1 and an embedding layer 2, the fiber layer 1 includes a first metal sintered felt, the embedding layer 2 includes a second metal sintered felt, and a metal powder sintered body embedded in the pores of the second metal sintered felt away from the metal sintered felt. The embedded fluid transport membrane includes a two-layer structure with different porosities, and the embedding layer 2 includes metal fibers and metal particles, with a high density and low surface roughness. The fiber layer 1 is composed of pure metal fibers, which retains the original characteristics of high porosity and low fluid transport resistance of the metal sintered felt. Figure 2 The layers are for illustration only and do not represent the actual thickness ratio.

[0036] It should be noted that, in order to describe the technical solution more specifically, the steps described in the following embodiments do not strictly correspond to the steps described in the content of the invention.

[0037] Example 1

[0038] A method for preparing an embedded fluid transport membrane comprises the following steps:

[0039] S1, preparing metal sintered felt: using a sedimentation method, for example, to evenly lay titanium fibers into a felt, wherein the titanium fibers have a diameter of 22 μm, a length of 5 mm, and a mass surface density of 500 g / m 2 , vacuum sintering (i.e., first sintering) is performed under a vacuum degree of 0.001Pa argon partial pressure, the sintering temperature is 1150 degrees, and the sintering time is 2 hours. After sintering, it is taken out from the sintering furnace after cooling. Rolling (i.e., first rolling) is performed, and the rolled titanium fiber felt is a metal sintered felt with a thickness of 0.55mm and a porosity of 80%. The titanium fiber is preferably a cutting fiber.

[0040] S2, preparing metal slurry: 100 parts by weight of ethanol and 20 parts by weight of polyethylene glycol are mixed, 5 parts by weight of an anti-settling agent (Deurheo anti-settling agent) are added, titanium powder particles with a particle size of 30 μm-45 μm are added, and stirred to obtain a slurry. The volume ratio of the titanium powder particles to the slurry is 5%.

[0041] S3, embedding: the metal slurry is uniformly infiltrated (filled) into one surface of the metal sintered felt by spraying. The penetration depth of the metal slurry is 35% of the thickness of the metal sintered felt, i.e., 0.19 mm. After the infiltration is completed, the surface of the metal sintered felt is flattened with a scraper, and the metal slurry remaining on the surface of the metal sintered felt (i.e., the metal slurry higher than the surface of the metal sintered felt) is removed to obtain a green film.

[0042] S4, post-treatment: The green membrane is naturally dried in air at room temperature for 10 hours. The dried green membrane is degreased (degummed) under argon as a protective atmosphere and a pressure of 1 mbar, with a degreasing temperature of 500 degrees and a degreasing time of 6 hours. The degreased green membrane is sintered in a high vacuum (i.e., the second sintering, not the first sintering mentioned above) under a vacuum degree of 0.001Pa and an argon partial pressure, with a sintering temperature of 1100 degrees and a sintering time of 2 hours, and is sintered into a whole. The sintered green membrane is rolled, and the thickness after rolling is 0.45mm, and it is rolled to the required thickness. A smooth porous metal plane can be achieved by rolling, and the pores on the original surface of the metal sintered felt are filled with embedded powder particles to obtain an embedded fluid transport membrane.

[0043] Example 2

[0044] A method for preparing an embedded fluid transport membrane comprises the following steps:

[0045] S1, preparing metal sintered felt: using a sedimentation method, for example, to evenly lay stainless steel fibers into felt, wherein the stainless steel fibers have a diameter of 30 μm, a length of 25 mm, and a mass surface density of 500 g / m 2 , vacuum sintering (i.e., first sintering) is performed under a vacuum degree of 50-300Pa argon partial pressure, the sintering temperature is 1150 degrees, and the sintering time is 2 hours. After sintering, it is taken out from the sintering furnace after cooling. Rolling (i.e., first rolling) is performed, and the stainless steel fiber felt after rolling is a metal sintered felt with a thickness of 0.50mm and a porosity of 87%. The stainless steel fiber is preferably a cutting fiber.

[0046] S2, preparing metal slurry: 100 parts by weight of ethylene glycol and 20 parts by weight of polyvinyl alcohol are mixed, 5 parts by weight of an anti-settling agent (Arkema anti-settling agent) are added, stainless steel powder particles with a particle size of 30 μm-45 μm are added, and the mixture is stirred evenly to obtain a slurry. The volume ratio of the stainless steel powder particles to the slurry is 35%.

[0047] S3, embedding: the metal slurry is uniformly infiltrated (filled) into one surface of the metal sintered felt by spraying. The penetration depth of the metal slurry is 20% of the thickness of the metal sintered felt, i.e., 0.10 mm. After the infiltration is completed, the surface of the metal sintered felt is flattened with a scraper, and the metal slurry remaining on the surface of the metal sintered felt (i.e., the metal slurry above the surface of the metal sintered felt) is removed to obtain a green film.

[0048] S4, post-treatment: The green membrane is naturally dried in air at room temperature for 12 hours. The dried green membrane is degreased (degummed) under argon as a protective atmosphere and a pressure of 5mbar, with a degreasing temperature of 700 degrees and a degreasing time of 2 hours. The degreased green membrane is sintered (i.e., the second sintering, not the first sintering mentioned above) under a vacuum degree of 50-300Pa argon partial pressure, a sintering temperature of 1100 degrees, and a sintering time of 2 hours to sinter into a whole. The sintered green membrane is rolled, and the thickness after rolling is 0.40mm, and it is rolled to the required thickness. A smooth porous metal plane can be achieved by rolling, and the pores on the original surface of the metal sintered felt are filled by embedded powder particles to obtain an embedded fluid transport membrane.

[0049] Example 3

[0050] An embedded fluid transport membrane prepared in Example 1 includes a composite fiber layer 1 and an embedding layer 2, wherein the fiber layer 1 includes a first metal sintered felt, and the embedding layer 2 includes a second metal sintered felt, and a metal powder sintered body embedded in the pores of the second metal sintered felt away from the first metal sintered felt. The first metal sintered felt and the second metal sintered felt are integrally arranged and are a continuous and complete felt body, that is, the same piece of metal sintered felt. The metal powder is titanium powder, and the first metal sintered felt and the second metal sintered felt are made of titanium fibers laid into felts, which are made by first sintering and first rolling. The diameter of the titanium fiber is 22 μm, and the total thickness of the first metal sintered felt and the second metal sintered felt is 0.45 mm. The second metal sintered felt is embedded with a metal powder sintered body as a whole, and the thickness of the second metal sintered felt is 55% of the thickness of the first metal sintered felt, and the thickness of the second metal sintered felt is 0.16 mm. The surface roughness Ra of the second metal sintered felt away from the first metal sintered felt is 6.5 microns, and the porosity of this side is 45%.

[0051] Example 4

[0052] An embedded fluid transport membrane prepared in Example 2 includes a composite fiber layer 1 and an embedding layer 2, the fiber layer 1 includes a first metal sintered felt, the embedding layer 2 includes a second metal sintered felt, and a metal powder sintered body embedded in the pores of the second metal sintered felt away from the first metal sintered felt. The first metal sintered felt and the second metal sintered felt are integrally arranged to form a continuous and complete felt body, that is, the same piece of metal sintered felt. The metal powder is stainless steel powder, and the first metal sintered felt and the second metal sintered felt are made of stainless steel fibers laid into felts, which are made by first sintering and first rolling. The diameter of the stainless steel fiber is 30 μm, and the total thickness of the first metal sintered felt and the second metal sintered felt is 0.40 mm. The second metal sintered felt is embedded with a metal powder sintered body as a whole, and the thickness of the second metal sintered felt is 25% of the thickness of the first metal sintered felt, and the thickness of the second metal sintered felt is 0.08 mm. The surface roughness Ra of the second metal sintered felt away from the first metal sintered felt is 6.5 microns, and the porosity of this side is 45%.

[0053] Comparative Example 1

[0054] A commercially available fluid transport membrane uses titanium fibers of two different wire diameters to lay out two layers of titanium fiber felt with different pore sizes, and the two layers of titanium fiber felt with different pore sizes are stacked and compounded together to obtain the fluid transport membrane.

[0055] Example 5

[0056] The embedded fluid transport membrane prepared in Example 1 or 2, or the embedded fluid transport membrane in Example 3 or 4 is used in a proton exchange membrane electrolyzer. Furthermore, the ion exchange membrane electrolyzer can be selected as a proton exchange membrane electrolyzer. The metal slurry infiltration surface (the second metal sintered felt surface) of the embedded fluid transport membrane is contacted and bonded with the catalyst, and the other surface is contacted with the bipolar plate to electrolyze water to produce hydrogen.

[0057] The fluid transport membranes of Example 3 and Comparative Example 1 were subjected to the following tests:

[0058] The current density of the fluid transport membrane of Example 3 and Comparative Example 1 was tested, and the voltage-current density curve was plotted. Figure 3 When the voltage is 2V, the current density of the embedded fluid transport membrane (T1) of Example 3 reaches 2A / cm 2 The current density of the fluid transport membrane sample (B1) of Comparative Example 1 reached 1.1 A / cm 2 Compared with the pure felt product (B1) of Comparative Example 1, the current density of the product (T1) of Example 3 at a voltage of 2V is about twice as high, and the product performance is greatly improved.

[0059] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing an embedded fluid transport membrane, characterized in that: The following steps are involved: Step 1: infiltrating the metal slurry from the surface of the metal sintered felt, with the infiltration depth being less than the thickness of the metal sintered felt; Step 2: After the infiltration is completed, the metal slurry remaining on the surface of the metal sintered felt is removed to obtain a green film; Step three: drying, degreasing and sintering the green film to obtain an embedded fluid transport membrane.

2. The preparation method according to claim 1, characterized in that: In step three, drying is carried out in air or a protective atmosphere, the drying temperature is from room temperature to 140 degrees, and the drying time is 2-12 hours; degreasing is carried out under an inert gas or hydrogen as a protective atmosphere and a pressure of 0.5-10mbar, the degreasing temperature is 300-700 degrees, and the degreasing time is 2-24 hours; under a vacuum degree of 0.001Pa-1000Pa, the sintering temperature is 900-1200 degrees, and the sintering time is 2-12 hours.

3. The preparation method according to claim 2, characterized in that: In step three, the drying condition is air drying at room temperature for 8-12 hours; in the degreasing condition, the inert gas is helium, argon or nitrogen, and the pressure is 1-5 mbar; the sintering temperature is 980-1120 degrees.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step three, after the sintering is completed, the green film is rolled, and the thickness of the felt body after rolling is 0.2-0.6 mm.

5. The preparation method according to claim 1, characterized in that: In step one, the metal sintered felt is prepared by laying metal fibers into felt, performing a first sintering and a first rolling; under a vacuum degree of 0.001Pa-1000Pa, the first sintering temperature is 900-1200 degrees, and the first sintering time is 2-12h; the thickness of the felt body after the first rolling is less than or equal to 0.8mm.

6. The preparation method according to claim 5, characterized in that: The metal fiber includes fibers of the following metals: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel; the diameter of the metal fiber is less than or equal to 30 μm; the thickness of the metal sintered felt is less than or equal to 0.6 mm, and the porosity is greater than or equal to 60%.

7. The preparation method according to claim 1, characterized in that: In step 1, the metal slurry is prepared by mixing 100 parts by weight of a solvent and 10-30 parts by weight of a binder, adding 1-10 parts by weight of an anti-settling agent, adding metal powder, and stirring evenly to obtain a slurry; the volume ratio of the metal powder to the slurry is 5%-35%.

8. The preparation method according to claim 7, characterized in that: The metal powder includes powders of the following metals: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel; the particle size of the metal powder is less than or equal to 55 μm; the solvent is alcohol, acetone or water; the binder is polyvinyl alcohol, polyethylene glycol or vinyl acetate.

9. The preparation method according to claim 1, characterized in that: In step 1, the metal slurry is infiltrated into the metal sintered felt by spraying; the penetration depth of the metal slurry is less than or equal to 85% of the thickness of the metal sintered felt.

10. The preparation method according to claim 1 or 9, characterized in that: In step 1, the penetration depth of the metal slurry is 15%-50% of the thickness of the metal sintered felt.

11. An embedded fluid transport membrane, characterized in that: It includes a composite fiber layer and an embedding layer, the fiber layer includes a first metal sintered felt, the embedding layer includes a second metal sintered felt, and a metal powder sintered body embedded in the pores of the second metal sintered felt on a side away from the first metal sintered felt; the surface roughness Ra of the side of the second metal sintered felt away from the first metal sintered felt is less than or equal to 7 microns.

12. The embedded fluid transport membrane according to claim 11, characterized in that The first metal sintered felt and the second metal sintered felt are integrally arranged to form a continuous complete felt body.

13. The embedded fluid transport membrane according to claim 11 or 12, characterized in that: The metal powder includes powders of the following metals: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel; the first metal sintered felt and the second metal sintered felt are made of metal fibers laid into felts, which are made through a first sintering and a first rolling; the metal fibers include fibers of the following metals: titanium, nickel, iron, titanium alloy, nickel alloy or iron alloy, and the iron alloy includes stainless steel.

14. The embedded fluid transport membrane according to claim 13, characterized in that The diameter of the metal fiber is less than or equal to 30 μm; the total thickness of the first metal sintered felt and the second metal sintered felt is 0.2-0.6 mm.

15. The embedded fluid transport membrane according to claim 11, characterized in that The entire second metal sintered felt is embedded with a metal powder sintered body, and the thickness of the second metal sintered felt is 15%-55% of the thickness of the first metal sintered felt.

16. Use of the embedded fluid transport membrane prepared by the preparation method of any one of claims 1 to 10, or the embedded fluid transport membrane of any one of claims 11 to 15 in an ion exchange membrane electrolytic cell.

17. The use according to claim 16, characterized in that The ion exchange membrane electrolysis cell is a proton exchange membrane electrolysis cell.